THE DIVISION OF THE AMIRATES INTO GROUPS BEFORE TUG‘LUQ TEMUR KHAN’S CAMPAIGN TO MOVAROUNNAHR AND THE BEGINNING OF AMIR HUSAYN'S POLITICAL ACTIVITY (ANALYSIS OF SOURCES) - Hakimov Adhambek (Web of Journals Publishing, 2025)
In this article highlights of the division of the amirates into groups before Tug‘luq Temur Khan’s campaign to Movarounnahr and the beginning of Amir Husayn's political activity (analysis of sources).
Keywords: Amirate, Movarounnahr, political activity, historical sources.